2005
DOI: 10.1111/j.1365-294x.2005.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring coyote population dynamics by genotyping faeces

Abstract: Reliable population estimates are necessary for effective conservation and management, and faecal genotyping has been used successfully to estimate the population size of several elusive mammalian species. Information such as changes in population size over time and survival rates, however, are often more useful for conservation biology than single population estimates. We evaluated the use of faecal genotyping as a tool for monitoring long-term population dynamics, using coyotes (Canis latrans) in the Alaska … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 53 publications
2
117
1
1
Order By: Relevance
“…Traditionally, survival has been difficult to estimate, much less monitor, for rare and elusive species. The ability to use molecular data to track known individuals can either replace or augment traditional efforts to monitor survival [16]. For instance, naturally shed feathers of Eastern imperial eagles Aquila heliaca have been used in a microsatellite analysis to identify individuals, monitor population turnover and estimate annual survivorship over a four-year period [17].…”
Section: Category I Diagnostic Molecular Markers For Traditional Popmentioning
confidence: 99%
“…Traditionally, survival has been difficult to estimate, much less monitor, for rare and elusive species. The ability to use molecular data to track known individuals can either replace or augment traditional efforts to monitor survival [16]. For instance, naturally shed feathers of Eastern imperial eagles Aquila heliaca have been used in a microsatellite analysis to identify individuals, monitor population turnover and estimate annual survivorship over a four-year period [17].…”
Section: Category I Diagnostic Molecular Markers For Traditional Popmentioning
confidence: 99%
“…Oliveira and J.M.B. Duarte samples to study wildlife populations involved sample collections conducted in cold climate regions (-20° to 10°C) (e.g., Frantz et al, 2003;Creel et al, 2003;Prugh et al, 2005) and/or the animal was observed at a distance until defecation, when the samples were collected in a fresh state, or the samples were collected from nests (e.g., Morin et al, 2001;Nsubuga et al, 2004). Weather and sample collection conditions such as those described are not realistic for many Neotropical species, such as deer of the genus Mazama.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the presence of these animals may be confirmed through the identification of their faeces, avoiding the elevated costs of capture and its possible damages (Wayne and Morin, 2004). Faecal analysis allows the monitoring of populations, their movements (Kohn and Wayne, 1997;Taberlet et al, 1997;Prugh et al, 2005), and provides diet-related information (Farrel et al, 2000).…”
mentioning
confidence: 99%
“…In the last decade, a large number of population studies have been based on faecal DNA analysis (Taberlet et al, 1997;Wasser et al, 1997;Palomares et al, 2002;Riddle et al, 2003;Deagle et al, 2005;Prugh et al, 2005).…”
mentioning
confidence: 99%